Impacts of Sodium/Glucose Cotransporter-2 Inhibitors on Circulating Uric Acid Concentrations: A Systematic Review and Meta-Analysis - Abolfazl Akbari; Mahdi Rafiee; Thozhukat Sathyapalan; Amirhossein Sahebkar (Journal of Diabetes Research)
Background. Several trials have assessed the antihyperglycemic effects of sodium/glucose cotransporter-2 inhibitors (SGLT2i) in patients with type 2 diabetes mellitus (T2DM). We conducted a quantitative analysis to assess the impact of SGLT2is on serum uric acid (SUA) in patients with T2DM. Methods. Placebo-controlled trials published before 13 August 2021 were identified by searching PubMed, Embase, Web of Science, and Scopus. The intervention group received SGLT2i as monotherapy or add-on treatment, and the control group received a placebo that was replaced with SGLT2i. Clinical trials providing changes in SUA were included. The mean change of SUA, glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), and body weight were calculated (PROSPERO CRD42021287019). Results. After screening of 1172 papers, 59 papers were included in the systematic review. A total of 55 trials (122 groups) of 7 types of SGLT2i on patients with T2DM were eligible for meta-analysis. All SGLT2is significantly decreased SUA levels compared with the placebo groups: empagliflozin mean difference MD=−40.98 μmol/L, 95% CI [-47.63, -34.32], dapagliflozin MD=−35.17 μmol/L, 95% CI [-39.68, -30.66], canagliflozin MD=−36.27 μmol/L, 95% CI [−41.62, −30.93], luseogliflozin MD=−24.269 μmol/L, 95% CI [-33.31, -15.22], tofogliflozin MD=−19.47 μmol/L, 95% CI [−27.40, −11.55], and ipragliflozin MD=−18.85 μmol/L, 95% CI [−27.20, −10.49]. SGLT2i also decreased FPG, body weight, and HbA1c levels. SUA reduction persisted during long-term treatment with SGLT2i (except for empagliflozin), while the SUA reduction was affected by the duration of diabetes. Conclusions. SGLT2i can be a valid therapeutic strategy for patients with T2DM and comorbid hyperuricemia. Besides reducing FPG, body weight, and HbA1c, SGLT2i can significantly decrease SUA levels compared to placebo (Total MD=−34.07 μmol/L, 95% CI [-37.00, -31.14]).